Formation of the honeycomb-like electrodes by the regime of pulsating overpotential in the second range - Nebojša D. Nikolić; Goran Branković; Miomir G. Pavlović (Journal of Electrochemical Science and Engineering, 2012)
In this study the honeycomb-like copper structures electrodeposited by the regime of pulsating overpotential in the second range were analyzed by the technique of scanning electron microscopy. The overpotential amplitude of 1000 mV, deposition pulse of 1 s, and pause durations of 1, 5, 10 and 15 s were selected for the production of this type of structures. The size of holes which remained upon detachment of hydrogen bubbles do not depend on the length of pause duration. On the other hand, the change in morphology of electrodeposited copper around holes from cauliflower-like agglomerates of copper grains to degenerated dendrites is observed when pause duration was increased. Effects of the application of the regime of pulsating overpotential in the second range on the formation of the honeycomb-like structures were less pronounced than the effects attained by the application of the same regime in the millisecond range. However, they were more pronounced than those attained by electrodeposition in the regime of constant potential.